HUBUNGAN PENDIDIKAN AGAMA ISLAM DAN POLITIK KEKUASAAN DI INDONESIA - ana cahayani fatimah (Fitrah, 2022)
Implementation of an effective, efficient and targeted Islamic education process requires the linkage of several elements such as: adequate educational resources, institutions that play an active role in accommodating, direct and indirect support from government institutions and policies because achieving educational goals requires optimal support from the community. various aspects so that the education process can be carried out in accordance with the objectives of the National Education System Law No. 20 of 2003 article 12 paragraph (1) letter a. Although the emergence of Islamic education actually did not come from power, but from religious teachings which were then judged to be good so that they were applied and became the philosophy of the state. Still, Islamic education is in the grip of power. As in establishing a boarding school or institution, it is required to ask permission from the power. Thus, Islamic education and power cannot be separated because there is an interaction that requires and depends on each other.